Din?mica geomorfol?gica do semi?rido Delagedo Alto - Bahia: estudo de tr?s de inselbergsrepresentativos da regi?o de Milagres - Rios, Irialinne Queiroz (2017)
The residual crystalline reliefs, called inselbergs, and the flat and low surfaces that cover them, still present a poorly understood morphogenesis. These geomorphological features in the state of Bahia, particularly in the Milagres region, have not yet been adequately studied, mainly, in regards to the morphology, mechanisms and correlated processes. The research aims to identify and characterize the dominant geomorphic processes and its resulting forms based on the study of the three representative inselbergs from the Milagres region ? Lagedo Alto. It intends to still describe and analyze the inherited morphology of these reliefs, as well as conduct a comparative analysis of the form and smaller features developed on them. Finally, the objective presents a contribution to the understanding of the current geomorphologic dynamics in the semi-arid region. To this end, it was necessary to proceed methodologically in distinct ways, through the realization of literature review, surveying cartographic instrumental, interpretation and analysis of photographs and satellite images, field and laboratory works. Based on the results obtained it was possible to admit that the landscape from the inselbergs fields of Milagres and Lagedo Alto received influences by a trend of lineaments, presenting a structure that favored the dissection process, along with the alternation between denudational phases. The morphological analysis carried out was permitted to identify the significant tectonic influence in the current landscape structuring, also certified through observations and descriptions done in the field. Dissecting and fracturing features are common among inselbergs. It became evident that the geometry of the reliefs and features developed about them are intimately associated structural factors, regional and local, respectively. The current evolution of the forms is conditioned by much more efficient mechanic processes